(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
We investigated the effect of natural pupil and wavefront aberration of the eye on the binocular summation. Nine volunteers took part in this study. Continuous recording of natural pupil diameters under monocular and binocular conditions was performed during each examination; contrast sensitivity, both distant and near visual acuity, and refraction. The pupil diameters were measured with an infrared pupillometer FP-10000 (TMI). Aberrometry measurements were performed with ARK-10000 (Nidek). Zernike coefficients were recalculated for the pupil diameters under the monocular and binocular conditions with Schwiegerling’s method of recalculating the expansion coefficient. Significant differences were found between the monocular and the binocular contrast sensitivity at the spatial frequencies greater than or equal to 6 c/deg (p < 0.05). The binocular summation ratio significantly heightened with the increase of the spatial frequencies (p < 0.05). The monocular visual acuity, both distant and near, was significantly worse than the binocular acuity (p < 0.01). Mean pupil diameters examined under the monocular condition significantly increased as compared to the binocular condition (p < 0.0001). With the increases in the pupil diameters, the optical aberrations significantly increased (p < 0.05). These results suggest that the effect of pupil size emphasizes binocular summation